2001
DOI: 10.1097/00125817-200101000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Functional brain imaging study of mathematical reasoning abilities in velocardiofacial syndrome (del22q11.2)

Abstract: Purpose: Children with velocardiofacial syndrome (VCFS) often have deficits in mathematical reasoning. Previous research has suggested that structural abnormalities in the parietal lobe region might underlie these deficits. The present study utilized functional magnetic resonance imaging (fMRI) to explore the relationship between brain function and mathematical performance in VCFS. Methods: Eight children with VCFS and eight comparison subjects underwent fMRI scanning and completed an arithmetic computation ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 25 publications
(32 reference statements)
5
50
0
Order By: Relevance
“…Thus, our findings replicated most of those previously reported, which include volume reductions in occipital, parietal, temporal and cerebellar regions (e.g., Eliez, Blasey, Menon, White, Schmitt, & Reiss, 2001;Eliez, Blasey, Schmitt, White, Hu, & Reiss, 2001;Eliez, Schmitt, White, & Reiss, 2000;Kates et al, 2001). In our sample, the gray matter analysis showed that the most extensive areas of reduced volume in the brains of children with DS22q11.2 were found in regions from the anterior aspects of the medial cerebellum through the parahippocampal, fusiform, and lingual regions, up through the cuneus, precuneus, posterior corpus callosum, posterior parietal lobes, and following the cingulum from posterior to a small medial region of its anterior aspect.…”
Section: Neural Substrate Changes In Ds22q112supporting
confidence: 92%
“…Thus, our findings replicated most of those previously reported, which include volume reductions in occipital, parietal, temporal and cerebellar regions (e.g., Eliez, Blasey, Menon, White, Schmitt, & Reiss, 2001;Eliez, Blasey, Schmitt, White, Hu, & Reiss, 2001;Eliez, Schmitt, White, & Reiss, 2000;Kates et al, 2001). In our sample, the gray matter analysis showed that the most extensive areas of reduced volume in the brains of children with DS22q11.2 were found in regions from the anterior aspects of the medial cerebellum through the parahippocampal, fusiform, and lingual regions, up through the cuneus, precuneus, posterior corpus callosum, posterior parietal lobes, and following the cingulum from posterior to a small medial region of its anterior aspect.…”
Section: Neural Substrate Changes In Ds22q112supporting
confidence: 92%
“…Multiple independent groups have reported that youth with VCFS have difficulty in visual spatial problem solving [Swillen et al, 1999;Bearden et al, 2001;Lajiness-O'Neill et al, 2005], and these deficits are most likely due to the alterations in parietal lobe gray/white volumes [Eliez et al, 2000b;Kates et al, 2001] and frontal-parietal connectivity [Barnea-Goraly et al, 2003] that have been described. For example, Eliez et al [2001] conducted a fMRI study of math reasoning in eight children with VCFS. Their results indicate that children with VCFS showed less activation than did controls in the angular gyrus, a posterior parietal brain region typically activated during such tasks.…”
Section: Cognitive Relative Weaknessesmentioning
confidence: 99%
“…In addition, increased activation was observed in the left supramarginal gyrus as a function of task difficulty. Eliez et al [2001] concluded that youth with VCFS may utilize an atypical and less effective circuit for completing math problems.…”
Section: Cognitive Relative Weaknessesmentioning
confidence: 99%
“…Although not exclusively the case, recent research has focused on explicitly computational aspects of the numerical domain, namely arithmetic and simple mathematics. Such tasks have been employed in order to understand the neural and, to some extent, the genetic basis of the problems (Eliez et al, 2001;Kesler, Menon, & Reiss, 2006;Molko, Cachia, Riviere, Mangin, Bruandet, LeBihan, Cohen, & Dehaene, 2004;Rivera, Menon, White, Glaser, & Reiss, 2002).…”
mentioning
confidence: 99%